Katabasis : a novel - Kuang, R. F. (Rebecca F.) (Harper Voyager, an imprint of HarperCollins Publishers, 2025)
"Alice Law has only ever had one goal: to become one of the brightest minds in the field of Magick. She has sacrificed everything to make that a reality: her pride, her health, her love life, and most definitely her sanity. All to work with Professor Jacob Grimes at Cambridge, the greatest magician in the world. That is, until he dies in a magical accident that could possibly be her fault. Grimes is now in Hell, and she's going in after him. Because his recommendation could hold her very future in his now incorporeal hands and even death is not going to stop the pursuit of her dreams.... Nor will the fact that her rival, Peter Murdoch, has come to the very same conclusion. With nothing but the tales of Orpheus and Dante to guide them, enough chalk to draw the Pentagrams necessary for their spells, and the burning desire to make all the academic trauma mean anything, they set off across Hell to save a man they don't even like. But Hell is not like the storybooks say, Magick isn't always the answer, and there's something in Alice and Peter's past that could forge them into the perfect allies...or lead to their doom"--